An evidence map of psychosocial interventions for the earliest stages of bipolar disorder. (June 2015) - Vallarino, Martine; Henry, Chantal; Etain, Bruno; Gehue, Lillian J; Macneil, Craig; Scott, Elizabeth M; Barbato, Angelo; Conus, Philippe; Hlastala, Stefanie A; Fristad, Mary; Miklowitz, David J; Scott, Jan
Summary: Depression, schizophrenia, and bipolar disorder are three of the four most burdensome problems in people aged under 25 years. In psychosis and depression, psychological interventions are effective, low-risk, and high-benefit approaches for patients at high risk of first-episode or early-onset disorders. We review the use of psychological interventions for early-stage bipolar disorder in patients aged 15–25 years. Because previous systematic reviews had struggled to identify information about this emerging sphere of research, we used evidence mapping to help us identify the extent, distribution, and methodological quality of evidence because the gold standard approaches were only slightly informative or appropriate. This strategy identified 29 studies in three target groups: ten studies in populations at high risk for bipolar disorder, five studies in patients with a first episode, and 14 studies in patients with early-onset bipolar disorder. Of the 20 completed studies, eight studies were randomised trials, but only two had sample sizes of more than 100 individuals. The main interventions used were family, cognitive behavioural, and interpersonal therapies. Only behavioural family therapies were tested across all of our three target groups. Although the available interventions were well adapted to the level of maturity and social environment of young people, few interventions target specific developmental psychological or physiological processes (eg, ruminative response style or delayed sleep phase), or offer detailed strategies for the management of substance use or physical health.